Global Species Diversity Patterns of Polypodiaceae Under Future Climate Changes - Sibo Huang; Gangmin Zhang; Wenpan Dong (Plants)
Global change influences species diversity patterns. Compared with seed plants, ferns are more sensitive to temperature and humidity changes and are an ideal group for studying species diversity patterns under future climate changes. Polypodiaceae, which has important ecological and application value, such as medicinal and ornamental value, is one of the most widely distributed fern families, with rich species diversity. Here, we explore the changes in the species diversity patterns of Polypodiaceae and their influencing factors. We collected more than 300,000 data points on the distribution of Polypodiaceae to map actual current species diversity patterns. We used Maxent to establish current and future potential species distribution models using 20 predictors and determined the current species diversity patterns using the actual current species diversity patterns and current potential species distribution model method. Multiple linear regression and random forest models were used to evaluate the effects of climate factors on the species diversity patterns of Polypodiaceae. We evaluated the effects of future climate changes on the species diversity of Polypodiaceae. The species diversity of Polypodiaceae increased gradually from higher to lower latitudes and the centers were concentrated in the low latitudes of tropical rainforests. There were four distribution centers across the world for Polypodiaceae: central America, central Africa, southern Asia, and northern Oceania. The species diversity of Polypodiaceae was greatly affected by precipitation factors rather than temperature factors. Under future climate change scenarios, species diversity is expected to shift and accumulate toward the equator in mid-to-low latitudes. Species diversity is projected to remain concentrated in low-latitude regions but will tend to aggregate towards higher altitude areas as global temperatures rise, with precipitation during the warmest season identified as the most influential factor.